KINETIC OF ION EXCHANGE IN ROUGH SYSTEMS PART 1: QUASI-HOMOGENEOUS DIFFUSION MODEL - Armijo C., Javier (2002)
The quasi homogeneous diffusion model is used to simulate the ion exchange kinetics in batch systems. The theoretical equation predicts that rate exchange is controlled by the ratio weight of the ion exchanger to volume of solution and the resistances to mass transfer in the particle and in the liquid.